Pendidikan Etika Bermedia Sosial Melalui Literasi Media Anti Hoax, Hate Speech dan Bullying - Wa Ode Lusianai; La Ode Muhammad Golok Jaya; Aryuni Salpiana Jabar (Jurnal PkM Pengabdian kepada Masyarakat, 2021)
Social media has become a platform for throwing issues at each other, which eventually make the community is invaded with various unclear and untrusted informations. Lack of awareness to create comfort and peaceful in the society through the use of healthy information encourages the present of this service program. Youth in RT 1 Kelurahan Mokoau as the main target of this activity should be able to be the driving force of information democracy, in fact they still have limited understanding in consuming and disseminating information as well as the ability to select and produce quality informations. The lack of ethics in using social media encourage the rise of fake news (hoaxes), hate speeches and bullies that currently become trend. For this reason, community service oriented activities would be the solution to the problem. This solution was implemented through training activities to shape partners' understanding and knowledge of the use of social media. After the training, there was a change in partners’ understanding and ability in knowing and identifying hoaxes, hate speeches and bullies in social media. Awareness in controlling the use of updates, shares, and likes features on social media began to grow. This activity was not only documented in video, but also published in online media. Through this service program, there comes a  social movement called healthy use of social media as a responsibility form in minimizing the misuse of information in the community with instagram account @antihoaxandhatespeech and facebook @antiHoax Bullying.